2015
DOI: 10.1186/s13104-015-1074-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with depressive symptoms among post-partum mothers in Nepal

Abstract: BackgroundPost-partum depression is a common complication of women after childbirth. The objective of this study was to determine the prevalence of and factors associated with depressive symptoms among post-partum mothers attending a child immunization clinic at a maternity hospital in Kathmandu, Nepal.MethodsThis cross-sectional study was conducted among 346 post-partum mothers at six to ten weeks after delivery using systematic random sampling. Mothers were interviewed using a semi-structured questionnaire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
54
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 35 publications
14
54
2
1
Order By: Relevance
“…In addition to that the current studies confirmed previous studies findings that stressful life such as family problem , week relation with husband or his family , previous psychological problems specially anxiety , exhausts , pregnancy depression, tearful and lake of sleep , and family history of PPD either first degree relative or second degree relative , (1-7) in Nepal studies the authors reported that there is relation between PPD and early contractions during pregnancy andmaternity blues after seven days from delivery, (2,39) in Turkey study the authors confirmed the relation between PPD and antepartum depressive symptoms which assessed byHADS-D , and they reported that thinking in committing suicidal during pregnancy is a high risk factors in developing PPD (odds ratio 6.99,CI 2.08-1545 23.49), (7,40,41) similar results were found in Singapore study where the authors reported high prevalence of PPD among women with previous psychological problems. (1,37,38) Regarding planning pregnancy and baby gender , the results of the current study showed significant association between developing PPD and unplanned pregnancy (p=0.01), this consistent with Turkey study .…”
Section: )supporting
confidence: 90%
See 2 more Smart Citations
“…In addition to that the current studies confirmed previous studies findings that stressful life such as family problem , week relation with husband or his family , previous psychological problems specially anxiety , exhausts , pregnancy depression, tearful and lake of sleep , and family history of PPD either first degree relative or second degree relative , (1-7) in Nepal studies the authors reported that there is relation between PPD and early contractions during pregnancy andmaternity blues after seven days from delivery, (2,39) in Turkey study the authors confirmed the relation between PPD and antepartum depressive symptoms which assessed byHADS-D , and they reported that thinking in committing suicidal during pregnancy is a high risk factors in developing PPD (odds ratio 6.99,CI 2.08-1545 23.49), (7,40,41) similar results were found in Singapore study where the authors reported high prevalence of PPD among women with previous psychological problems. (1,37,38) Regarding planning pregnancy and baby gender , the results of the current study showed significant association between developing PPD and unplanned pregnancy (p=0.01), this consistent with Turkey study .…”
Section: )supporting
confidence: 90%
“…Previous studies in Nepal and Saudi Arabia reported the prevalence of PPD 30-33% with cut off score ≥10,(2,3) also the results from Pakistan and India studies the prevalence was between 11%-40% , while in other studies with cut of ≥ 12 the prevalence was 6%-12% ,(2,12,13)and 15.4% in Turkish study with cut off ≥ 13, (7)this Varity in the prevalence rate could be due to the difference cut off, multi-cultural and multi-social factors, sample size and methods. (2,3,7,12,14,15) The findings of current study showed that mother aged more than 40 years are more likely to develop PPD than younger mother , similar results were found in Singapore Nepal and Canada studies the authors reported high prevalence of PPD among women aged 35-40 ,(1,2,16)in contrast in Turkey and Canada studies the authors reported high prevalence of PPD among young mother , (2,7,17,18,19) while in Saudi Arabia study the association was between older and younger age. Several studies investigated the association between PPD occurrence and sociodemographic data (mother's education and occupation , monthly income and father's education and occupation), (6,(20)(21)(22)(23)(24)(25)(26) where the results showed contradictory evidence (1,2,3,7), in Nepal ,Singapore, turkey and Saudi study there was no association between mother's education level, occupation and low monthly income and PPD , (1,2,3,7)while in other studies there was positive association between PPD and mother's lower education , being a housewife , and lower monthly income,(2,3,7 27-32)also in 2007 study the authors reported significant association between lower partner education and occupationand PPD , (7,33) the current study showed consistent with previous study regarding mother low educational level and controversy result regarding mother occupation and monthly income, where the high prevalence of PPD was between working mothers and high monthly income.…”
Section: Result:-mentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Similar study done in other countries showed the prevalence 23.77%, 30% and 9.2%. 1,11,16 The prevalence was quite low in the present study compared to the above studies. This may be due to good and proper postnatal care was given to the women in the study area.…”
Section: Discussioncontrasting
confidence: 75%
“…10 PND has been associated with tragic outcomes, such as maternal suicide and infanticide. 11 In spite of so many adverse events associated with postpartum depression almost half of the postnatal depression cases goes unnoticed by the health care providers. The major reason being unrevealing of symptoms by the mother due to fear.…”
Section: Introductionmentioning
confidence: 99%